Utilization of coconut residue in chocolate coated confections - Liao, Christine V.; Galvez, Flor Crisanta F. (1995.)
Chocolate coated confections utilizing formulated coconut residue as center were produced. The effects of center type used (caramel and cream paste) and sugar to sapal ration (3:4, 2:4 and 1:4) on consumer acceptability of the products were studied. Appearance, sweetness, coconut flavor, chocolate flavor, mouthfeel and overall acceptability were evaluated by 24 consumer panelists using nine-point hedonic scales. Water activity and moisture content determinations were likewise conducted. A two-month shelf life stability (in terms of microbial load and acceptability to consumers) was done also on the products stored at 18-25°C. Results were analyzed using analysis of variance and mean computation. Results indicated that all samples were acceptable to consumers although the caramel-centered products received higher scores. The caramel-centered chocolates registered lower activities and were found acceptable to consumers for three weeks when stored at 18-25°C. The cream paste-centered chocolates kept for less than two weeks at the same temperature of storage.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products